Virtue acquisition: The paradox of striving. Issue 2 (2nd April 2016) - Snow, Nancy
Abstract: Aristotelian-inspired accounts of virtue acquisition stress guided practice and habituated action to develop virtue. This emphasis on action can lead to the 'paradox of striving'. The paradox occurs when we try too hard to act well and thereby spoil our efforts. I identify four forms of striving—forcing, impulsivity, overthinking, and holding oneself to too high a standard—and explain how they can cause our actions to miss the virtuous mark. Though neo-Aristotelians can offer remedies for these ills, I turn in the rest of this article to explore an approach to virtue inspired by the life and work of Mahatma Gandhi. Gandhi stresses receptivity to personal transformation and turning inward through meditative practice as ways in which we can attain the inner states needed for virtuous action. In consequence, a Gandhian approach offers a rather different analysis of the paradox of striving than that given by neo-Aristotelianism.